Quantifying the Environmental Design Trades for a State-of-the-Art Turbofan Engine - Evangelia Maria Thoma; Tomas Grönstedt; Xin Zhao (Aerospace, 2020)
Aircraft and engine technology have continuously evolved since their introduction and significant improvement has been made in fuel efficiency, emissions, and noise reduction. One of the major issues that the aviation industry is facing today is pollution around the airports, which has an effect both on human health and on the climate. Although noise emissions do not have a direct impact on climate, variations in departure and arrival procedures influence both CO2 and non-CO2 emissions. In addition, design choices made to curb noise might increase CO2 and vice versa. Thus, multidisciplinary modeling is required for the assessment of these interdependencies for new aircraft and flight procedures. A particular aspect that has received little attention is the quantification of the extent to which early design choices influence the trades of CO2, NOx, and noise. In this study, a single aisle thrust class turbofan engine is optimized for minimum installed SFC (Specific Fuel Consumption). The installed SFC metric includes the effect of engine nacelle drag and engine weight. Close to optimal cycles are then studied to establish how variation in engine cycle parameters trade with noise certification and LTO (Landing and Take-Off) emissions. It is demonstrated that around the optimum a relatively large variation in cycle parameters is allowed with only a modest effect on the installed SFC metric. This freedom in choosing cycle parameters allows the designer to trade noise and emissions. Around the optimal point of a state-of-the-art single aisle thrust class propulsion system, a 1.7 dB reduction in cumulative noise and a 12% reduction in EINOx could be accomplished with a 0.5% penalty in installed SFC.